DNA-marker based identification of the RPV3 gene determining downy mildew resistance in grapevines - E. T. Ilnitskaya; M. V. Makarkina; S. V. Tokmakov; L. G. Naumova (Вавиловский журнал генетики и селекции)
Downy mildew is one of the most common fungal diseases of the vine, caused by Plasmopara viticola. An effective way to control the spread of the pathogen is to cultivate resistant varieties. Cultivars of Vitis vinifera, being the basis of high-quality viticulture, practically do not possess genetic resistance to P. viticola, so screening for resistance donors is an important stage in breeding. One of the major resistance loci to downy mildew, the Rpv3 gene, was identified in the genotype of a complex interspecific hybrid of grapes Bianca. Later, it was found that this gene had seven haplotypes of resistance inherited from North American grape species, and that it was possible to identify the allelic status of the gene using DNA-markers UDV305, UDV737. However, only two haplotypes can be combined in one diploid form. To determine the Rpv3 gene in the grape gene pool we, using these markers, studied 35 different genotypes of grapevines, most of which are interspecies cultivars. Three varieties with known allelic status of the Rpv3 gene (Dunavski lazur, Noah, Seyve Villard 12-375) were included in the study as reference genotypes. The genotypes were studied through polymerase chain reaction with separation of amplification products by capillary electrophoresis in automatic genetic analyzer ABI Prism 3130. In the studied grape cultivars DNA marker analysis indentified the Rpv3 gene in sixteen genotypes of interspecific origin, including haplotype Rpv3299-279 found in twelve varieties, Rpv3321-312 – in three, and haplotype Rpv3null-271 – in one variety. Seyve Villard 12-375 turned out to be the donor of resistance gene in the most of the genotypes carrying Rpv3 in this study. The obtained data can be useful in selection of mildew resistant grape varieties and screening for hybridization pairs.